2016
DOI: 10.1158/1078-0432.ccr-15-2242
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide, Thalidomide, and Pomalidomide Reactivate the Epstein–Barr Virus Lytic Cycle through Phosphoinositide 3-Kinase Signaling and Ikaros Expression

Abstract: Purpose Lenalidomide, thalidomide, and pomalidomide (LTP) are immunomodulatory agents approved for use in multiple myeloma, but in some settings, especially with alkylating agents, an increase in Hodgkin’s lymphoma (HL) and other secondary primary malignancies (SPM) has been noted. Some of these malignancies have been linked to Epstein-Barr virus (EBV), raising the possibility that immunomodulatory drugs disrupt latent EBV infection. Experimental Design We studied the ability of LTP to reactivate latently in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…S5E, lanes 4-6). Although Pom has been reported to induce EBV lytic replication in certain other EBV-infected cell lines such as B95.8 and Daudi, 48 we did not detect induction of lytic replication (assessed by BMRF1 induction) in Akata cells by Pom in these experiments (Fig. S5E, lanes 1-3), nor did it have a substantial effect on the levels of BMRF1 lytic protein induced by anti-human IgG (Fig S6E, lanes 4-6).…”
Section: Pom Upregulates Surface Markers In Ebv-infected Cell Linesmentioning
confidence: 52%
“…S5E, lanes 4-6). Although Pom has been reported to induce EBV lytic replication in certain other EBV-infected cell lines such as B95.8 and Daudi, 48 we did not detect induction of lytic replication (assessed by BMRF1 induction) in Akata cells by Pom in these experiments (Fig. S5E, lanes 1-3), nor did it have a substantial effect on the levels of BMRF1 lytic protein induced by anti-human IgG (Fig S6E, lanes 4-6).…”
Section: Pom Upregulates Surface Markers In Ebv-infected Cell Linesmentioning
confidence: 52%
“…Numerous studies have reported that the PI3K/AKT pathway plays an important role in metastasis through the regulation of EMT [23][24][25]. Therefore, the PI3K inhibitor LY294002 [26][27][28][29] was used to detect the effect of the PI3K/AKT pathway on AGK-induced RCC proliferation and metastasis. As shown in Fig.…”
Section: Agk Promotes Rcc Proliferation and Metastasis Via The Pi3k/amentioning
confidence: 99%
“…A variety of strategies to induce lytic viral gene expression so as to facilitate the killing of EBV-associated tumors have been investigated for many years (3-5, 7, 26-31). In some approaches, the hope is that a lytic inducer will activate a viral thymidine kinase or protein kinase that will phosphorylate ganciclovir, poisoning the cellular DNA polymerase such that mitotic cells will be killed (5,7,(31)(32)(33). Other strategies have aimed at the upregulation of immunodominant viral antigens recognized by cytotoxic T cells or the selective concentration of radiopharmaceuticals in tumor tissue (3,4).…”
Section: Discussionmentioning
confidence: 99%